Stuck [videorecording (DVD)] - Esposito, Giancarlo; Madigan, Amy; Ashanti, 1980-; Thomas, Riley (Vision Films, 2019)
An original pop musical about six commuters who get trapped together on a New York City subway. Through the power of music, they learn about each other's lives and, in turn, have a profound impact on one another. Connecting across lines of race, culture, and class in a way that only situations of circumstance or happenstance can create, this will be a day that none of them will ever forget.